No relationship between most polymorphisms of steroidogenic acute regulatory (StAR) gene with polycystic ovarian syndrome - Azadeh-Sadat Nazouri; Mona Khosravifar; Ali-Asghar Akhlaghi; Marzieh Shiva; Parvaneh Afsharian (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine women's disorders in reproductive age. Hyperandrogenism has a critical role in the etiology of PCOS and it can cause fault in Steroidogenesis process. During steroidogenesis, steroidogenic acute regulatory protein (StAR) seems to increase the delivery of cholesterol through mitochondrial membrane. Therefore, polymorphisms of StAR might effect on this protein and play a role in the etiology of PCOS. Objective: The aim of this study was to investigate the association between StAR SNPs with PCOS. Thus, seven polymorphisms in this gene: rs104894086, rs104894089, rs104894090, rs137852689, rs10489487, rs104894085 were detected. Materials and Methods: In this case control study, 45 PCOS women, 40 male factor/unexplained infertile women, and 40 fertile women as two control groups were participated from 2008-2012. Polymorphisms were detected using restriction fragment length polymorphism (PCR-RFLP) method. Results: Heterozygote genotyping for rs137852689 SNP (amino acid 218 C > T) was only seen in seven PCOS patients, one in normal ovulatory women, and five in male factor/unexplained infertile women (15.5%, 2.5%, 12.5%, respectively) (p= 0.12). While, it has shown no association between other SNPS with PCOs. Conclusion: The RFLP results for seven chosen SNPs, which located in exon 5 and 7 showed normal status in three groups, it means no heterozygous or homozygous forms of selected SNPs were observed. So, it seems evaluation of the active amino acid sites should be investigated and also the study population should be increased.